Synthesis and Spectral Studies of Lanthanide(III) Complexes with 4-Methoxy- 4'-N,N-dimethylaminodiphenyl Azomethine and Diphenyl Sulfoxide - RAJENDRAN, G.; USHA DEVI, K.G. (Asian Journal of Chemistry, 2010)
Twelve new complexes of Pr(III), Nd(III), Eu(III), Sm(III), Gd(III) and Dy(III) with the ligands 4-methoxy-4'-N,N-dimethylaminodiphenylazomethine (MDDA) and diphenylsulphoxide (DPSO) with the compositions [Ln(MDDA)3(DPSO)x3] where X = NO3 or NCS- have been synthesized and characterized by metal estimation, elemental analysis, molar conductance and magnetic susceptibility measurements and IR and UV-Vis spectral studies and thermal analysis. Based on the data, appropriate structures are assigned for these complexes.